Age Is a Risk Factor for Gastroscopy-Assisted Capsule Endoscopy in Children - Jing Xie; Lu Ren; Defeng Liang; Liya Xiong; Liying Liu; Wanfu Xu; Sitang Gong; Lanlan Geng; Peiyu Chen; Hongli Wang (The Turkish Journal of Gastroenterology, 2024)
Background/Aims: The aim of this study was to explore the risk factors for the incidence of gastroscopy-assisted capsule endoscopy and the small bowel transit time in pediatric patients who underwent capsule endoscopy examination.